Parabolic Action of the Family of Jesus - Kunz, Claiton (Vox Scripturae - Revista Teológica Internacional, 2014)
Jesus used different teaching methods during his ministry. One of these was the method of parabolic actions, in like manner the symbolic actions of the prophets of the Old Testament. This research analyzes the text on the family of Jesus, according to the account of the Evangelist Mark (3.31-35), from the perspective of a parabolic action and seek answers to he question of the special meaning of the text.